Post-earthquake fire assessment of reinforced concrete frame structures - Vitorino, Hugo (2022)
Earthquakes can cause several catastrophic events and the consequences of fires in urban areas can be even worse than the consequences of the earthquake itself. Several numerical models were developed with SAFIR—software that models the behaviour of structures subject to fire for reinforced concrete (RC) frames to study their post-earthquake fire behaviour. First, a calibration was performed to validate the modelling strategy. Subsequently, two different frame typologies were considered, and a parametric study was carried out considering as the main variables the location and configuration of the damage caused by the earthquake and the location of the fire within the structure. The results show that the damaged RC frames have a lower fire resistance when compared with the undamaged frames. It was observed that the difference in time until collapse between an undamaged frame and a heavily damaged frame can be higher than 2 h. This observation is particularly relevant since, after a large earthquake, the rescue teams are generally overloaded, and consequently the response times are higher than that. This, combined with the reduction of the fire resistance of the reinforced concrete elements caused by the earthquake, can lead to increased severity and ultimately to the losses.